A simplified analysis procedure for performance-based earthquake engineering of buildings. (1st November 2017) - Huang, Yin-Nan; Whittaker, Andrew S.; Hamburger, Ronald O.
Highlights: A linear analysis procedure was developed to predict distributions of peak linear/nonlinear structural responses. The procedure applies for low- to medium-rise framing systems of low to moderate global ductility. Sample buildings constructed with moment frames, braced frames and shear walls were analyzed. Abstract: Accurate assessment of the seismic performance of buildings and the computation of direct and indirect economic losses resulting from earthquake shaking requires the use of analysis procedures that reliably predict distributions of peak structural response quantities, including story drift, floor velocity, and floor acceleration. A linear analysis procedure was developed for this purpose and is suitable for application to low- and medium-rise buildings of regular configuration. The analysis procedure was calibrated using results of nonlinear response-history analysis of 3-, 5-, 9-, and 15-story models of three dimensional archetype buildings constructed with moment frames, braced frames and shear walls.